Student Creativity Program (PKM) Workshop for Informatics Management Polsri 2026: Enhancing Students’ Capacity to Design PKM Ideas: Workshop Program Kreativitas Mahasiswa (PKM) Manajemen Informatika Polsri 2026: Peningkatan Kapasitas Mahasiswa Merancang Gagasan PKM - Rahman, M Arief; Ferizka Tiara Devani; Lailatur Rahmi; Ade Sukma Wati (STIKES Columbia Asia Medan, 2026)
This community service article discusses the Student Creativity Program (PKM) Workshop for Informatics Management students of Politeknik Negeri Sriwijaya in 2026. The activity aimed to increase students’ capacity to design PKM ideas that are creative, logical, collaborative, and relevant to the problems of society and technology development. The method used a participatory workshop consisting of needs identification, material preparation, online implementation, discussion, idea clinic, and follow-up reflection. The workshop introduced the substance of PKM, proposal logic, theme selection, team collaboration, and the PKM-GFT scheme as a written futuristic idea that emphasizes visionary, realistic, solution-oriented, long-term, and broad-impact concepts. The results showed that students obtained a clearer understanding of PKM schemes, the characteristics of feasible ideas, and the importance of transforming simple observations into structured proposals. The activity also encouraged students to prepare ideas based on problems, novelty, benefits, and implementation logic. This workshop implies that continuous mentoring is needed to strengthen students’ proposal-writing skills, creativity, and competitiveness in PKM submission